Diode‐Like Selective Enhancement of Carrier Transport through Metal–Semiconductor Interface Decorated by Monolayer Boron Nitride. Issue 36 (28th July 2020) - Jaiswal, Hemendra Nath; Liu, Maomao; Shahi, Simran; Wei, Sichen; Lee, Jihea; Chakravarty, Anindita; Guo, Yutong; Wang, Ruiqiang; Lee, Jung Mu; Chang, Chaoran; Fu, Yu; Dixit, Ripudaman; et al.
Abstract: 2D semiconductors such as monolayer molybdenum disulfide (MoS2 ) are promising material candidates for next‐generation nanoelectronics. However, there are fundamental challenges related to their metal–semiconductor (MS) contacts, which limit the performance potential for practical device applications. In this work, 2D monolayer hexagonal boron nitride ( h ‐BN) is exploited as an ultrathin decorating layer to form a metal–insulator–semiconductor (MIS) contact, and an innovative device architecture is designed as a platform to reveal a novel diode‐like selective enhancement of the carrier transport through the MIS contact. The contact resistance is significantly reduced when the electrons are transported from the semiconductor to the metal, but is barely affected when the electrons are transported oppositely. A concept of carrier collection barrier is proposed to interpret this intriguing phenomenon as well as a negative Schottky barrier height obtained from temperature‐dependent measurements, and the critical role of the collection barrier at the drain end is shown for the overall transistor performance. Abstract : A novel diode‐like selective enhancement of the carrier transport through a metal–insulator–semiconductor (MIS) contact is revealed through comparison with a conventional metal–semiconductor contact on a single monolayer MoS2 triangular domain. The MIS contact exploits monolayer hexagonal boron nitride as an ultrathin decorating layer added between MoS2 and the metal contact.